Mangrove Planting and Blue Economy Education as an Effort to Preserve Coastal Ecosystems on Pari Island, Thousand Islands - Diah Pranitasari; Gatot Prabantoro; Erna Lovita; Diana Supriati; Devvy Rusli (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Mangrove ecosystems play a strategic role in protecting coastlines from abrasion, supporting biodiversity, and mitigating climate change through blue carbon storage. Environmental pressures have degraded mangroves across Indonesia's coasts, including Pari Island, where observations revealed mild abrasion, declining vegetation, and limited understanding of blue economy-based conservation. This activity aimed to raise environmental awareness and support coastal rehabilitation through mangrove planting and blue economy education on Pari Island, Seribu Islands, in collaboration with Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, Indonesia Blue Economy, and Maritim Muda Indonesia. A participatory approach was applied, comprising environmental outreach, blue economy education, planting technique training, and direct planting. Forty-seven participants planted 500 Rhizophora mucronata seedlings, and the average score increased from 61.5 (pre-test) to 87.3 (post-test). Beyond improving knowledge of mangrove functions and blue economy concepts, the activity strengthened collaboration among universities, environmental communities, and local residents for sustainable coastal development. These findings indicate that combining education with field action can raise awareness and support coastal rehabilitation.